Estimating harvested rainwater at greenhouses in south Portugal aquifer Campina de Faro for potential infiltration in Managed Aquifer Recharge - Costa, Luís (2015)
The Campina de Faro (CF) aquifer system, located on the south coast of Portugal, is an important source of groundwater, mostly used for agriculture purposes. In some areas, this multi-layered aquifer is contaminated with high concentration of nitrates, possibly arising from excessive usage of fertilizers, reaching to values as high as 300 mg/L.